1995
DOI: 10.1046/j.1471-4159.1995.64041528.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acetylcholinesterase Secretion in Neuronal Cultures and Regulation by High K+ and Soluble Factors from Target Cells

Abstract: We have observed that cultured neurons from chick spinal cord and the neuroblastoma hybrid line 108CC15 released lower amounts of acetylcholinesterase (AChE) when compared with the parental line, N18TG2. AChE activity extracted by hypotonic buffer, which can be regarded as the source of the released enzyme, was considerably higher in the parental than in the hybrid 108CC15 (respectively, ∼80% and ∼40% of cellular activity). On the other hand, evaluation of ectocellular, with respect to total, AChE activity sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(68 reference statements)
1
11
1
Order By: Relevance
“…The basal level of AChE mRNA was higher in the neuroblastoma‐glioma NG108CC15 cells than in N18TG2, in agreement with their relative AChE activities (Melone et al . 1987; Biagioni et al . 1995) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basal level of AChE mRNA was higher in the neuroblastoma‐glioma NG108CC15 cells than in N18TG2, in agreement with their relative AChE activities (Melone et al . 1987; Biagioni et al . 1995) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, HSP70 transcripts were highly increased after heat shock in the two cell lines; PRiMA transcripts were unaffected. In NG108CC15 cells, which express a higher level of AChE activity than N18TG2 cells (Biagioni et al . 1995), we found no change in total AChE transcripts or in the AChE R variant; in contrast, we observed a modest increase of AChE transcripts in N18TG2, and a sixfold increase of AChE R , which reached approximately the same level as in NG108CC15 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A further consideration pointing to AChE as a possible modulatory molecule for cell behavior is its ability to be associated to different cell compartments; it is known that in different cell types and possibly in relation to developmental stage the enzyme is either secreted in the extracellular space or remains associated to the plasma membrane. In neuroblastoma cultures its cellular localization has been related to different stages of neuronal differentiation (Melone et al, 1987), and the comparative analysis of AChE release in different neuronal populations has suggested that acquisition of a cholinergic phenotype is characterized by a low level of AChE release (Biagioni et al, 1995; Coleman and Taylor, 1996). The data reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This allows the investigation of AChE morphogenetic action, avoiding the possible interference of self‐produced neurotransmitter. This neuroblastoma clone exhibits some neuronal traits, such as the presence of tetrodotoxin‐sensitive voltage‐gated Na + channels and cholinergic receptors (De Jaco et al, 2000); it expresses moderate amounts of the tetrameric AChE form that is mostly secreted in the extracellular medium (Biagioni et al, 1995).…”
mentioning
confidence: 99%